Recognition of prior learning program in improving human resource in Bojonegoro district: an open government analysis - Alifa, Siti Nur; Wulandari, Septi; Lukita, Cahya (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research aims to analyze open government by looking at the implementation of the Village Recognition of Prior Learning (RPL) program in Bojonegoro Regency through a process of collaboration, transparency, and participation. Increasing the capacity of Human Resources (HR) is needed in facing the demands of better public services. This research method uses descriptive qualitative research. Primary data sources consist of open-ended interviews, as well as observation. While secondary data sources come from documentation studies obtained from the research location. The technique of determining informants was carried out by purposive sampling, namely selecting based on criteria on informants who play a role in the Village RPL program, the Secretary of the Village Community Empowerment Office, the Head of the Community Empowerment Division, Surabaya State University and Yogyakarta State University and Village Officials. Data validation uses the data triangulation method. The results of this study indicate that the RPL Desa program in government openness has a collaborative process between the stakeholders involved, transparency of new student screening information data, and participation of village development activists as community servants facing problems in completing their studies. Supporting factors lead to the use of scholarships in higher education with recognition of experience, online learning, and RPL program organizers from quality universities. The inhibiting factors are seen from the declining commitment and motivation of students in participating in the lecture process and the difficulty of time management between college work.